Is Digital GOOD for providing water security?- A case study of India - et al., Dr Lakshmi Shankar Iyer (International Journal of Advanced Science and Technology, 2019)
We live in an urbanizing world. Large cities with population greater than 750,000 would represent US$21.8 trillion in economic activity or 47.7% global GDP. These cities are already home to 1.7 billion people, about 24% of the world’s population. By the year 2050, it is expected that ninety percent of the world’s urban population growth will occur in Asia and Africa. Economic growth goes hand-in-hand with the urban growth. With the population increase in cities, there is a need for ample and consistent supply of water. The supply of water is a fundamental component of the environmental, economic and social health of cities. There is a huge investment of US$90 billion a year in water supply infrastructure to ensure delivery of clean water to the citizens. If the current trend continues, the volume of urban water need will have to go up by 80% by the year 2030. In this context, The World Economic Forum classified water security as one of the greatest threats to global prosperity in the year 2014.